Tendencies of climatic changes for thermal conditions in the coastal areas of the Okhotsk Sea in last decades - Igor D. Rostov; Elena V. Dmitrieva; Alexander A. Vorontsov (Известия ТИНРО)
The sea surface temperature (SST) variability in recent conditions of climatic warming is analyzed for coastal areas of the Okhotsk Sea on the data of regular observations on hydrometeorological stations in 1980-2016 and NOAA_OI_SST_V2 reanalysis data, taking into account the climate indices variations. The data series are analyzed using the methods of Empirical Orthogonal Functions (EOF), cluster analysis and correlation analysis. The SST fluctuations with period of 2-5 years prevailed in the year-to-year variability on the background of longer cycles and irregular changes with three periods of different thermal regime: cold (1977-1987), transitional (1988-2003), and warm (2004-2016). These periods were observed for the whole sea area and coincided with similar changes of the air temperature and sea ice. A tendency to warming was the most noticeable in the last 15 years when the average growth rate of mean annual SST was 0.17oC per 10 years, with 1.5-2.0 times higher values for some stations. The positive SST trend in summer was approximately twice higher than in winter; the trend increased 3-fold from northern to southern areas of the Okhotsk Sea. The trend contributed 46 % of the mean annual SST dispersion. Large-scale process of the SST regime changing is described by the first EOF mode and could be parametrized by PDO, NPI and OKH climatic indices.